2009
DOI: 10.1093/sleep/32.4.491
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia with Objective Short Sleep Duration is Associated with a High Risk for Hypertension

Abstract: Insomnia with short sleep duration is associated with increased risk of hypertension, to a degree comparable to that of other common sleep disorders, e.g., SDB. Objective sleep duration may predict the severity of chronic insomnia a prevalent condition whose medical impact has been apparently underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
499
7
21

Year Published

2011
2011
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 663 publications
(568 citation statements)
references
References 33 publications
41
499
7
21
Order By: Relevance
“…For example, sleep duration has been prospectively associated with weight gain, while poor sleep quality has been associated with metabolic syndrome, hypertension, and coronary heart disease. [14][15][16][17][18][19] Neuroendocrine changes caused by poor sleep partially account for these relationships, 20 but behavioral factors related to sleep disturbance, such as decreased physical activity, may also play a role.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…For example, sleep duration has been prospectively associated with weight gain, while poor sleep quality has been associated with metabolic syndrome, hypertension, and coronary heart disease. [14][15][16][17][18][19] Neuroendocrine changes caused by poor sleep partially account for these relationships, 20 but behavioral factors related to sleep disturbance, such as decreased physical activity, may also play a role.…”
Section: S C I E N T I F I C I N V E S T I G a T I O N Smentioning
confidence: 99%
“…Insomnia disorder with objective short sleep durationis associated with increasing incidence of hypertension and negatively impacts the variability of blood pressure and heart rate, which has been associated with increased cardiovascular mortality 5,6,7 . A cross-sectional analysis revealed that insomnia with objective short sleep duration is associated with an increased risk of diabetes 8 .…”
mentioning
confidence: 99%
“…Patients with fatigue were more likely to be institutionalized and had increased mortality in the subsequent year. 101 In some studies, delirium was reported in up to half of patients, especially in the first week after ischemic stroke. 102,103 This delirium can prolong hospital stay and increases risk of dementia and admission to an institution.…”
Section: Obstructive Sleep Apnea and Rehabilitation Outcomementioning
confidence: 99%